Unraveling the Mechanism of Impaired Osteogenic Differentiation in Osteoporosis: Insights from ADRB2 Gene Polymorphism - Olga Krasnova; Julia Sopova; Anastasiia Kovaleva; Polina Semenova; Anna Zhuk; Daria Smirnova; Daria Perepletchikova; Olga Bystrova; Marina Martynova; Vitaly Karelkin; Olga Lesnyak; Irina Neganova (Cells)
Osteoporosis is characterized by increased resorption and decreased bone formation; it is predominantly influenced by genetic factors. G-protein coupled receptors (GPCRs) play a vital role in bone homeostasis, and mutations in these genes are associated with osteoporosis. This study aimed to investigate the impact of single nucleotide polymorphism (SNP) rs1042713 in the ADRB2 gene, encoding the beta-2-adrenergic receptor, on osteoblastogenesis. Herein, using quantitative polymerase chain reaction, western immunoblotting, immunofluorescence assays, and flow cytometry, we examined the expression of ADRB2 and markers of bone matrix synthesis in mesenchymal stem cells (MSCs) derived from osteoporosis patient (OP-MSCs) carrying ADRB2 SNP in comparison with MSCs from healthy donor (HD-MSCs). The results showed significantly reduced ADRB2 expression in OP-MSCs at both the mRNA and protein levels, alongside decreased type 1 collagen expression, a key bone matrix component. Notably, OP-MSCs exhibited increased ERK kinase expression during differentiation, indicating sustained cell cycle progression, unlike that going to HD-MSC. These results provide novel insights into the association of ADRB2 gene polymorphisms with osteogenic differentiation. The preserved proliferative activity of OP-MSCs with rs1042713 in ADRB2 contributes to their inability to undergo effective osteogenic differentiation. This research suggests that targeting genetic factors may offer new therapeutic strategies to mitigate osteoporosis progression.